Transnational and Decolonial Feminist Insights Into the Neoliberalization of Estonian Academia - Redi Koobak; Raili Marling (Studia Litteraria et Historica, 2024)
Since the 1990s Estonia has been characterized by the acceptance of neoliberal values, as an antidote to the Soviet past. Neoliberal practices, like quantification and market- orientation, have permeated most spheres of society, including academia. There has been very little critical reflection on the epistemic inequalities created by this academic model for Estonia as a semi-peripheral country. In this article, the authors aim to place the neoliberalization of academia within a broader framework of colonial practices within global knowledge production, continuing their previous work on the blind spots of transnational feminism  and intersections of feminisms and neoliberalism. Building on insights developed within transnational and decolonial  feminism, the authors propose three interventions into neoliberal academic culture: telling better stories, practicing slow scholarship to tease apart complex colonial entanglements and using creative writing practices.